2007
DOI: 10.1111/j.1745-6584.2006.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sea‐Level Rise on Ground Water Flow in a Coastal Aquifer System

Abstract: The effects of sea-level rise on the depth to the fresh water/salt water interface were simulated by using a density-dependent, three-dimensional numerical ground water flow model for a simplified hypothetical fresh water lens that is similar to shallow, coastal aquifers found along the Atlantic coast of the United States. Simulations of sea-level rise of 2.65 mm/year from 1929 to 2050 resulted in an increase in water levels relative to a fixed datum, yet a net decrease in water levels relative to the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 18 publications
2
65
0
Order By: Relevance
“…In contrast, the observation wells in the middle of aquifer area showed small or insignificant influences of sea level on groundwater level. Previous studies on the impacts of future sea level rise on groundwater quality and groundwater resources have reported that these will mainly take place along the coastline, main rivers and drainage canals in low-lying aquifers [5,6,70,71]. Those studies also reported the influence of stream types and tides on the groundwater level of aquifers along the coastline, with higher groundwater levels in response to sea level rise causing more discharge into the streams.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, the observation wells in the middle of aquifer area showed small or insignificant influences of sea level on groundwater level. Previous studies on the impacts of future sea level rise on groundwater quality and groundwater resources have reported that these will mainly take place along the coastline, main rivers and drainage canals in low-lying aquifers [5,6,70,71]. Those studies also reported the influence of stream types and tides on the groundwater level of aquifers along the coastline, with higher groundwater levels in response to sea level rise causing more discharge into the streams.…”
Section: Discussionmentioning
confidence: 69%
“…These DRN cells remove water from the groundwater system when the water table intersects land surface, thus preventing the water table from rising above the land surface. This method does not provide for the development of new surface-water bodies but does allow for a more physically realistic analysis of the response of the underlying freshwater-saltwater interface in response to a changing sea-level position because it is the altitude of the water table (or surface-water expressions of the water table) above local sea level that generally determines the depth to the underlying freshwater-saltwater interface (Masterson and Garabedian, 2007;Werner and Simmons, 2009). …”
Section: Surface Seepagementioning
confidence: 99%
“…It is understood that as sea-level rises, the water table in shallow coastal aquifer systems also will rise, and depending on the thickness of the vadose zone, the water table may intersect land surface (Masterson and Garabedian, 2007). To account for this condition, head-dependent flux boundaries in the Drain (DRN) package in SEAWAT (Langevin and others, 2007) were assigned to every model cell above sea level with the stage height specified at the land-surface altitude of each cell (Sanford and others, 2012).…”
Section: Surface Seepagementioning
confidence: 99%
See 1 more Smart Citation
“…), water supply from coastal aquifers in Florida and elsewhere (Anderson et al 1988;Rao et al 2004;Spechler 1994), as well in the prediction of the effects of sea level rise in these aquifers (Masterson 2004;Masterson and Garabedian 2007;Rozell and Wong 2010).…”
Section: Introductionmentioning
confidence: 99%